Diet composition, niche overlap and partitioning of five sympatric rhinolophid bats in Southwestern China during summer - Dai, Wentao; Li, Aoqiang; Chang, Yang; Liu, Tong; Zhang, Lin; Li, Jun; Leng, Haixia; Li, Zhongle; Jin, Longru; Sun, Keping; Feng, Jiang (Frontiers in Ecology and Evolution, 2023)
Understanding trophic niche differentiation is critical for exploring interspecific competition and stable coexistence among morphologically similar sympatric species. Bats are an ideal model for studying trophic niche differentiation among species because of their high taxonomic and ecological diversities, as well as their special life history traits. Although many factors can affect bat trophic niches, few studies have combined multiple factors to investigate the influences on bat trophic niches. In this study, we analyzed the summer diet and potential influencing factors of five sympatric rhinolophid bats in southwestern China: Rhinolophus macrotis, Rhinolophus osgoodi, Rhinolophus ferrumequinum, Rhinolophus affinis, and Rhinolophus pusillus. All five species mainly fed on Lepidopteran and Dipteran insects, with a large trophic niche breadth for each species and a low degree of dietary overlap. With the exception of R. affinis and R. pusillus, significant differences in diet composition were detected among species, which indicated relatively low interspecific competition. Canonical correspondence analysis showed that both echolocation calls and body size significantly affected interspecific diet differentiation, while wing morphology and bite force had relatively weak effects. This study suggests that the combined effects of multiple factors may drive trophic niche differentiation among five rhinolophid bat species in the study area.